Sodium-ion battery positive electrode material and preparation method thereof, sodium-ion battery and power-related equipment
By adopting a core shell structure on the positive electrode material of sodium ion battery and using the coating technology of lanthanum and calcium, the surface compound with electron conduction/ion/oxygen storage functions is constructed, the problem of lattice oxygen release of O3 structure positive electrode material at high voltage is solved, and the cycle stability and energy density of the battery are improved.
Patent Information
- Application Number
- CN202411769915.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing O3 structure sodium ion battery positive electrode material has the release of lattice oxygen at high voltage, resulting in the dissolution of transition metals, affecting the processing process and service life of the battery cell.
The sodium ion battery cathode material adopts a core shell structure, wherein the chemical formula of the core is NaaNixFeyMnzM1-x-y-zO2 and the chemical formula of the shell is NaLarCa1-rO2. The surface compound with electron conduction/ion/oxygen storage functions is constructed by coating lanthanum and calcium elements.
It effectively reduces the residual alkali on the particle surface, inhibits the release of lattice oxygen, improves the cycle stability and energy density of the positive electrode material, and extends the service life of the battery.
Smart Images

Figure CN119601630A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to a sodium ion battery positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art
[0002] At present, new energy lithium-ion batteries have been widely used in the 3C, power battery and energy storage markets due to their high energy density and long life. However, as the abundance of lithium resources is limited and mining is difficult, as lithium elements are continuously consumed, new chemical systems are urgently needed to supplement the application market of lithium-ion batteries. Sodium-ion batteries are rocking-chair secondary batteries, which are consistent with the principles of lithium-ion batteries. Sodium and lithium belong to the same main group elements and exhibit similar "rocking-chair" electrochemical charging and discharging behaviors in battery operation. During the charging process of sodium-ion batteries, sodium ions are removed from the cathode and embedded in the anode, while electrons pass through the external circuit. The more sodium ions embedded in the anode, the higher the charging capacity; during discharge, the opposite process occurs, and the more sodium ions return to the positive electrode, the higher the discharge capacity. In addition, the cost of lithium-ion batteries is much higher than that of sodium-ion batteries, so sodium-ion batteries will play an equally important role in the new energy industry.
[0003] Among the positive electrode materials of sodium ion batteries, the O3 structure positive electrode material has a higher initial sodium content, so the passenger capacity is relatively high, but the existing O3 structure sodium ion battery positive electrode material technology still has many technical problems. For example, the residual alkaline substances sodium hydroxide and sodium carbonate on the surface of the particles, which everyone is more concerned about, will react with the electrolyte, and the release of lattice oxygen under high voltage will lead to the dissolution of transition metals, which will bring serious problems to the processing and service life of the battery cell. Therefore, it is necessary to reduce the residual alkali on the surface of the particles and inhibit the release of lattice oxygen.
[0004] At present, the modification measures for positive electrode materials are basically centered around doping and coating, using doping to enhance the stability of the crystal structure and coating to improve the interface stability. However, the lattice oxygen release of positive electrode materials is mostly located on the surface of the particles. Many coating agents have little effect on the stability of the surface oxygen, and gas production is still serious. Therefore, it is necessary to construct a layer of material with ion conduction and storage of oxygen ions released from the lattice on the surface to solve the problems of short cycle life and gas production of O3 structure positive electrode materials. Summary of the invention
[0005] The purpose of this application is to provide a sodium ion battery positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment to solve the above problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] The present application provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material comprises a core and a shell, the shell covers the core; the chemical formula of the core is Na a Ni x Fe y Mn z M 1-x-y-z O2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1; the chemical formula of the shell is NaLa r Ca 1- r O2, where 0<r<1;
[0008] Optionally, in the core, the M element includes one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, and B.
[0009] The present application also provides a method for preparing a positive electrode material for a sodium ion battery, comprising:
[0010] The solutions of the nickel source, the manganese source, the iron source and the M element source are mixed, and then a pH adjuster is added, and a hydroxide precursor is obtained by a coprecipitation method.
[0011] The hydroxide precursor is mixed with a sodium source, and then first calcined, followed by cooling to obtain a first calcined product.
[0012] The first calcined product is mixed with a calcium source and a lanthanum source and then subjected to a second calcination to obtain the sodium ion battery positive electrode material.
[0013] Optionally, the nickel source includes nickel sulfate, the manganese source includes manganese sulfate, and the iron source includes iron sulfate.
[0014] Optionally, the M element source includes sulfates of one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, and B.
[0015] Optionally, the pH adjuster includes at least one of ammonia water and sodium hydroxide.
[0016] Optionally, the pH value of the system is adjusted to 8.0-12.0 using the pH adjuster.
[0017] Optionally, after the hydroxide precursor is prepared, a solid-liquid separation, washing and drying process is further included, and the temperature during the drying process is 100-300° C. and the time is 2-6 hours.
[0018] Optionally, the chemical formula of the hydroxide precursor is Ni x Fe y Mnz M 1-x-y-z (OH)2, wherein 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0.
[0019] Optionally, the chemical formula of the first calcined product is Na a Ni x Fe y Mn z M 1-x-y-z O2, where 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0.
[0020] Optionally, the mixing ratio of the hydroxide precursor and the sodium source is a molar ratio of metal cations to sodium ions in the hydroxide precursor of 1:n, wherein 0.95≤n≤1.4.
[0021] Optionally, the lanthanum source comprises La2O3.
[0022] Optionally, the calcium source includes CaCl2, CaCO3, CaO, Ca(OH), or CaF2.
[0023] Optionally, the lanthanum source and the calcium source are nanoscale particles.
[0024] Optionally, the first calcination is a multi-stage calcination; the multi-stage calcination process includes: raising the temperature to 400-550°C at a heating rate of 1.5-7°C / min for pre-sintering, and the pre-sintering time is 4-8h; then raising the temperature to 800-1100°C at a heating rate of 1.5-7°C / min for sintering, and the sintering time is 10-24h; cooling to room temperature after sintering.
[0025] Optionally, the calcination atmosphere of the first calcination includes air and oxygen.
[0026] Optionally, the second calcination temperature is 300-600° C. and the time is 5-10 hours. After the second calcination, the coating amount of the calcium element is 300-2000 ppm, and the coating amount of the lanthanum element is 300-2000 ppm.
[0027] The present application also provides a sodium ion battery, the raw materials of which include the sodium ion battery positive electrode material.
[0028] The present application also provides an electrical device, including the sodium ion battery.
[0029] Compared with the prior art, the beneficial effects of this application include:
[0030] The present application provides a positive electrode material for a sodium ion battery, wherein a compound having a perovskite structure containing La and Ca elements is coated on the surface of the particles, and the surface compound has the function of conducting electrons / ions / storing oxygen. Among them, on the one hand, the lanthanum element can change its physical and chemical properties by adjusting the crystal structure of the positive electrode material, thereby increasing the capacity of the battery, optimizing the crystal structure of the material, and thus increasing the overall capacity of the battery; at the same time, by stabilizing the crystal structure of the positive electrode material, the lanthanum element helps to inhibit undesirable phase changes during the charge and discharge process, thereby improving the cycle stability of the material. This is of great significance for extending the service life of sodium ion batteries. On the other hand, the calcium element may improve the structure of the positive electrode material of the sodium ion battery through a certain mechanism, thereby improving its overall performance. This improvement may include increasing the crystallinity of the material, reducing defects, etc.; and the introduction of the calcium element also helps to improve the thermal stability of the positive electrode material. Therefore, the positive electrode material for a sodium ion battery provided in the present application can reduce the residual alkali on the surface of the particles while also inhibiting the side reaction with the electrolyte, thereby improving the performance stability of the positive electrode material.
[0031] The preparation method provided in the present application is simple and convenient, does not require an additional water washing step, reduces energy consumption and can also obtain a positive electrode material with performance advantages.
[0032] The sodium ion battery provided by the present application has good energy density and cycle life, and does not produce gas during use. The electrical equipment provided by the present application has excellent electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0034] Figure 1 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0035] As used herein:
[0036] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0037] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0038] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0039] In these examples, parts and percentages are by mass unless otherwise indicated.
[0040] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0041] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0042] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0043] In a first aspect, the present application provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material comprising a core and a shell, the shell covering the core; the chemical formula of the core is Na a Ni x Fe y Mn z M 1-x-y-zO2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1; the chemical formula of the shell is NaLa r Ca 1-r O2, where 0<r<1.
[0044] Wherein a can be 0.9, 0.95, 1.0, 1.05, or any value greater than or equal to 0.9 and less than or equal to 1.05; x can be 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.99, or any value greater than 0 and less than 1.0 or any interval such as 0.1-0.9, 0.2-0.9, 0.3-0.9, 0.25-0.95, 0.3-0.99, etc. y can be 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.99, or any value or interval greater than 0 and less than 1.0, such as 0.1-0.9, 0.2-0.9, 0.3-0.9, 0.25-0.95, 0.3-0.99, etc. z can be 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.99, or any value or interval greater than 0 and less than 1.0, such as 0.1-0.9, 0.2-0.9, 0.3-0.9, 0.25-0.95, 0.3-0.99, etc. r can be 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.99, or any value or interval greater than 0 and less than 1.0, such as 0.1-0.9, 0.2-0.9, 0.3-0.9, 0.25-0.95, 0.3-0.99, etc.
[0045] In the core, the M element includes one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, and B.
[0046] In a second aspect, the present application also provides a method for preparing a positive electrode material for a sodium ion battery, comprising:
[0047] The solutions of the nickel source, the manganese source, the iron source and the M element source are mixed, and then a pH adjuster is added, and a hydroxide precursor is obtained by a coprecipitation method.
[0048] The hydroxide precursor is mixed with a sodium source, and then first calcined, followed by cooling to obtain a first calcined product.
[0049] The first calcined product is mixed with a calcium source and a lanthanum source and then subjected to a second calcination to obtain the sodium ion battery positive electrode material.
[0050] In an optional embodiment, the nickel source includes nickel sulfate, the manganese source includes manganese sulfate, and the iron source includes iron sulfate.
[0051] In an optional embodiment, the M element source includes sulfates of one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, and B.
[0052] In an optional embodiment, the pH adjuster includes at least one of ammonia water and sodium hydroxide.
[0053] In an optional embodiment, the pH value of the system is adjusted to 8.0-12.0 (.
[0054] Optionally, the pH value can be adjusted to 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, or any value between 8.0 and 12.0.
[0055] In an optional embodiment, the preparation of the hydroxide precursor further includes solid-liquid separation, washing, and drying processes, wherein the temperature during the drying process is 100-300° C. and the time is 2-6 hours.
[0056] Optionally, the temperature during the drying process may be 100° C., 150° C., 200° C., 250° C., 300° C., or any value between 100-300° C. The drying time may be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, or any value between 2-6 h.
[0057] In an optional embodiment, the chemical formula of the hydroxide precursor is Ni x Fe y Mn z M 1-x-y-z(OH)2, wherein 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0.
[0058] In an optional embodiment, the chemical formula of the first calcined product is Na a Ni x Fe y Mn z M 1-x-y-z O2, where 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0.
[0059] In an optional embodiment, the mixing ratio of the hydroxide precursor and the sodium source is a molar ratio of metal cations to sodium ions in the hydroxide precursor of 1:n, wherein 0.95≤n≤1.4.
[0060] Optionally, the molar ratio of metal cations to sodium ions in the hydroxide precursor can be 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, or any value between 1:0.95-1.4.
[0061] In an alternative embodiment, the lanthanum source comprises La2O3.
[0062] In an optional embodiment, the calcium source includes CaCl2, CaCO3, CaO, Ca(OH), and CaF2.
[0063] In an optional embodiment, the lanthanum source and the calcium source are nano-sized particles.
[0064] In an optional embodiment, the first calcination is a multi-stage calcination; the multi-stage calcination process includes: raising the temperature to 400-550°C at a heating rate of 1.5-7°C / min for pre-sintering, and the pre-sintering time is 4-8h; then raising the temperature to 800-1100°C at a heating rate of 1.5-7°C / min for sintering, and the sintering time is 10-24h; cooling to room temperature after the sintering is completed. During the multi-stage calcination process, the raw materials undergo physical and chemical changes at high temperatures, making the material structure more compact. Through two-step segmented calcination, the migration distance of lithium ions during high-temperature sintering can be significantly shortened, thereby improving the density of the material. In addition, through segmented calcination, the two oxides can generate single-phase lithium oxides, grain growth, and improved crystallinity. At the same time, multi-stage calcination can remove impurities and volatile substances in the raw materials and improve the purity of the materials. Ultimately, the prepared positive electrode material usually has better cycle stability.
[0065] Optionally, the heating rate during pre-sintering can be 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, 3.0℃ / min, 3.5℃ / min, 4.0℃ / min, 4.5℃ / min, 5.0℃ / min, 5.5℃ / min, 6.0℃ / min, 6.5℃ / min, 7.0℃ / min, or any value between 1.5-7℃ / min; the endpoint temperature of the pre-sintering can be 400℃, 430℃, 460℃, 490℃, 520℃, 550℃, or any value between 400-550℃; the pre-sintering time can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any value between 4-8h. The heating rate during sintering can be 1.5°C / min, 2.0°C / min, 2.5°C / min, 3.0°C / min, 3.5°C / min, 4.0°C / min, 4.5°C / min, 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, or any value between 1.5-7°C / min; the sintering temperature can be 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, 1020°C , 1040℃, 1060℃, 1080℃, 1100℃, or any value between 800-1100℃; the sintering time can be 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, 20h, 20.5h, 21h, 21.5h, 22h, 22.5h, 23h, 23.5h, 24h, or any value between 10-24h.
[0066] In an optional embodiment, the calcination atmosphere of the first calcination includes air and oxygen.
[0067] In an optional embodiment, the second calcination temperature is 300-600° C. and the time is 5-10 hours. After the second calcination, the coating amount of calcium element is 300-2000 ppm, and the coating amount of lanthanum element is 300-2000 ppm.
[0068] Optionally, the temperature of the second calcination may be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, or any value between 300-600°C.
[0069] Optionally, the coating amount of the calcium element after the second calcination can be 300ppm, 500ppm, 700ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm, or any value between 300-2000ppm; the coating amount of the lanthanum element after the second calcination can be 300ppm, 500ppm, 700ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm, or any value between 300-2000ppm.
[0070] In a third aspect, the present application also provides a sodium ion battery, the raw materials of which include the sodium ion battery positive electrode material.
[0071] In a fourth aspect, the present application also provides an electrical device, including the sodium ion battery.
[0072] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0073] Example 1
[0074] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0075] (1) Nickel sulfate, manganese sulfate, iron sulfate and aluminum sulfate solutions were mixed in a ratio of Ni:Fe:Mn:Al=40:20:35:5 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.8, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0076] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.4 Fe 0.2 Mn 0.35 Al 0.05(OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0077] (3) To Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 La2O3 with a particle size of 30-200nm and an addition amount of 1500ppm and CaO with a particle size of 30-200nm and an addition amount of 216ppm are added to the O2 material. After being mixed evenly, they are calcined at 450℃ for 6h to finally obtain the positive electrode material for sodium ion batteries. The SEM spectrum of the obtained positive electrode material particles is shown in Figure 1 shown.
[0078] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0079] Example 2
[0080] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0081] (1) Nickel sulfate, manganese sulfate, iron sulfate and titanium sulfate solutions were mixed in a ratio of Ni:Fe:Mn:Ti=30:20:45:5 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.8, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.3 Fe0.2 Mn 0.45 Ti 0.05 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0082] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.3 Fe 0.2 Mn 0.45 Ti 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Ti 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0083] (3) To Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Ti 0.05 La2O3 with a particle size of 30-200nm and an addition amount of 1500ppm and CaO with a particle size of 30-200nm and an addition amount of 433ppm are added to the O2 material. After being evenly mixed, they are calcined at 450°C for 6h to finally obtain the positive electrode material for sodium ion batteries.
[0084] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0085] Example 3
[0086] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0087] (1) Nickel sulfate, manganese sulfate, iron sulfate, aluminum sulfate and copper sulfate solution were mixed uniformly in a ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.3, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0088] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the above two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Ni was cooled with the furnace to obtain 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0089] (3) To you 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 La2O3 with a particle size of 30-200nm and an addition amount of 1500ppm and CaO with a particle size of 30-200nm and an addition amount of 216ppm are added to the O2 material. After being evenly mixed, they are calcined at 450°C for 6h to finally obtain the positive electrode material for sodium ion batteries.
[0090] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0091] Example 4
[0092] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0093] (1) Nickel sulfate, manganese sulfate, iron sulfate, aluminum sulfate and copper sulfate solution were mixed uniformly in a ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.4, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0094] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the above two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Ni was cooled with the furnace to obtain 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0095] (3) To you 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 La2O3 with a particle size of 30-200nm and an addition amount of 1500ppm and CaO with a particle size of 30-200nm and an addition amount of 865ppm are added to the O2 material. After being evenly mixed, they are calcined at 450°C for 6h to finally obtain the positive electrode material for sodium ion batteries.
[0096] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0097] Example 5
[0098] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0099] (1) Nickel sulfate, manganese sulfate, iron sulfate, aluminum sulfate and copper sulfate solution were mixed uniformly in a ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.8, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0100] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05(OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the above two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Ni was cooled with the furnace to obtain 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0101] (3) To you 0.35 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 La2O3 with a particle size of 30-200nm and an amount of 800ppm and CaO with a particle size of 30-200nm and an amount of 865ppm are added to the O2 material. After being evenly mixed, they are calcined at 450°C for 6h to finally obtain the positive electrode material for sodium ion batteries.
[0102] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0103] Example 6
[0104] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0105] (1) Nickel sulfate, manganese sulfate, iron sulfate and zinc sulfate solutions were mixed in a ratio of Ni:Fe:Mn:Cu:Zn=35:20:35:10 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.8, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.35 Fe 0.2 Mn 0.35 Zn0.1 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0106] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.35 Fe 0.2 Mn 0.35 Zn 0.1 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the above two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Ni was cooled with the furnace to obtain 0.35 Fe 0.2 Mn 0.35 Zn 0.1 O2, crush the material through a double roller mill, sieve through 300 mesh, and set aside.
[0107] (3) To you 0.35 Fe 0.2 Mn 0.35 Zn 0.1 O2 is added with La2O3 with a particle size of 30-200nm and an addition amount of 1500ppm, and CaO with a particle size of 30-200nm and an addition amount of 865ppm. After being mixed evenly, it is calcined at 450℃ for 6h to finally obtain the positive electrode material of the sodium ion battery.
[0108] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0109] Example 7
[0110] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0111] Different from Example 6, the sintering temperature in step (2) is increased to 980° C., and other parameters remain unchanged, and finally a sodium ion battery positive electrode material is obtained.
[0112] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0113] Example 8
[0114] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0115] The difference from Example 6 is that in step (3), Ni 0.35 Fe 0.2 Mn 0.35 Zn 0.1 Add La2O3 with a particle size of 30-200nm and an amount of 1500ppm to the O2 material, and CaO with a particle size of 30-200nm and an amount of 865ppm. After mixing evenly, calcine at 530℃ for 6h. Other parameters remain unchanged, and finally obtain the positive electrode material of the sodium ion battery.
[0116] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0117] Example 9
[0118] This embodiment provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0119] The difference from Example 1 is that the molar ratio of metal cations to Na ions in step (2) is changed to 1:1.0; other parameters remain unchanged, and finally a sodium ion battery positive electrode material is obtained.
[0120] The present embodiment also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a hard carbon negative electrode material. The electrolyte includes an organic solvent and a sodium salt. Propylene carbonate, ethylene carbonate, and dimethyl carbonate are mixed uniformly in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus ceramic coating film is used as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0121] Comparative Example 1
[0122] This comparative example provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0123] (1) Nickel sulfate, manganese sulfate, iron sulfate and aluminum sulfate solutions were mixed in a ratio of Ni:Fe:Mn:Al=40:20:35:5 to obtain a mixed solution, and then 2 mol / L ammonia water and sodium hydroxide solution were added to the solution to adjust the pH value of the mixed solution to 11.8, and then the hydroxide precursor Ni was obtained by coprecipitation. 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2, and filtered and washed, and then dried at 200°C for 5h to obtain a dried hydroxide precursor.
[0124] (2) The dried hydroxide precursor Ni obtained in step (1) is 0.4 Fe 0.2 Mn 0.35 Al 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering, and the atmosphere was air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h, and the atmosphere was air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05O2, the material is crushed by a roller mill and sieved with 300 mesh to obtain the positive electrode material of the sodium ion battery.
[0125] The comparative example also provides a sodium ion battery, the raw materials of which include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet, and the negative electrode sheet adopts a hard carbon negative electrode material, the electrolyte includes an organic solvent and a sodium salt, propylene carbonate, ethylene carbonate, and dimethyl carbonate are uniformly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus a ceramic coating film is used as a diaphragm, and the remaining steps are assembled into a sodium ion battery according to a conventional method, and the corresponding electrical performance test is carried out.
[0126] Comparative Example 2
[0127] This comparative example provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0128] The parameters in step (1) and step (2) in this comparative example are the same as those in Example 1, except that in step (3), the Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 1000ppm of nano-Al2O3 particles were added to the O2 material, mixed evenly, and then sintered at 450°C for 6h to obtain the positive electrode material for the sodium ion battery.
[0129] The comparative example also provides a sodium ion battery, the raw materials of which include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet, and the negative electrode sheet adopts a hard carbon negative electrode material, the electrolyte includes an organic solvent and a sodium salt, propylene carbonate, ethylene carbonate, and dimethyl carbonate are uniformly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then sodium hexafluorophosphate sodium salt is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus a ceramic coating film is used as a diaphragm, and the remaining steps are assembled into a sodium ion battery according to a conventional method, and the corresponding electrical performance test is carried out.
[0130] Comparative Example 3
[0131] This comparative example provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0132] The parameters in step (1) and step (2) in this comparative example are the same as those in Example 1, except that in step (3), the Na 1.01 Ni0.4 Fe 0.2 Mn 0.35 Al 0.05 1000ppm of nano-Al2O3 particles and 500ppm of MgO were added to the O2 material, mixed evenly, and sintered at 450°C for 6h to obtain the positive electrode material for the sodium ion battery.
[0133] This comparative example also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet; the negative electrode sheet adopts a hard carbon negative electrode material; the electrolyte includes an organic solvent and a sodium salt, and propylene carbonate, ethylene carbonate, and dimethyl carbonate are uniformly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus a ceramic coating film is used as a diaphragm, and the remaining steps are assembled into a sodium ion battery according to a conventional method, and the corresponding electrical performance tests are carried out.
[0134] Comparative Example 4
[0135] This comparative example provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0136] The parameters in step (1) and step (2) in this comparative example are the same as those in Example 1, except that in step (3), the Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 800 ppm of nano-Al2O3 particles and 700 ppm of MgO were added to the O2 material, mixed evenly, and sintered at 450°C for 6 hours to obtain the positive electrode material for the sodium ion battery.
[0137] This comparative example also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet; the negative electrode sheet adopts a hard carbon negative electrode material; the electrolyte includes an organic solvent and a sodium salt, and propylene carbonate, ethylene carbonate, and dimethyl carbonate are uniformly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus a ceramic coating film is used as a diaphragm, and the remaining steps are assembled into a sodium ion battery according to a conventional method, and the corresponding electrical performance tests are carried out.
[0138] Comparative Example 5
[0139] This comparative example provides a sodium ion battery positive electrode material, and the preparation method is as follows:
[0140] The parameters in step (1) and step (2) in this comparative example are the same as those in Example 1, except that in step (3), the Na 1.01 Ni 0.4 Fe 0.2 Mn 0.35 Al 0.05 1000ppm of nano-Al2O3 particles, 500ppm of MgO and 400ppm of ZrO were added to the O2 material, mixed evenly and sintered at 450°C for 6h to obtain the positive electrode material for the sodium ion battery.
[0141] This comparative example also provides a sodium ion battery, whose raw materials include the above-mentioned positive electrode material, binder, polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode slurry, which is coated on an aluminum foil to make a positive electrode sheet; the negative electrode sheet adopts a hard carbon negative electrode material; the electrolyte includes an organic solvent and a sodium salt, and propylene carbonate, ethylene carbonate, and dimethyl carbonate are uniformly mixed in a mass ratio of 1:1:1 under an inert atmosphere, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte; and a polyethylene film or a polyethylene plus a ceramic coating film is used as a diaphragm, and the remaining steps are assembled into a sodium ion battery according to a conventional method, and the corresponding electrical performance tests are carried out.
[0142] The electrical properties of the batteries prepared in Examples 1-9 and Comparative Examples 1-5 are shown in Table 1:
[0143] Table 1 Electrical properties of sodium ion batteries prepared in the examples and comparative examples
[0144]
[0145] It can be seen that in Examples 1-9 of the present application, the prepared sodium ion battery positive electrode material is coated with lanthanum and / or calcium. In Comparative Examples 1-5, Comparative Example 1 is a sodium ion battery prepared from the positive electrode material obtained when no coating is performed, Comparative Example 2 is a sodium ion battery prepared from the positive electrode material obtained when aluminum is coated, Comparative Example 3 is a sodium ion battery prepared when aluminum and magnesium are coated, Comparative Example 4 is a sodium ion battery prepared when aluminum and magnesium are coated, and Comparative Example 5 is a sodium ion battery prepared when aluminum, magnesium, and zirconium are coated.
[0146] On the one hand, it can be seen from Table 1 that in Examples 1-9, when lanthanum and / or calcium are coated, the amount of residual alkali on the surface of the positive electrode material is lower than that in Comparative Examples 1-5, which means that the positive electrode material is not easy to react with the electrolyte, thereby avoiding irreversible degradation of the crystal structure of the positive electrode material. Reducing the amount of residual alkali on the surface can reduce these harmful interfacial reactions, thereby maintaining the structural stability of the positive electrode material. This can also be reflected in the 200 cycles in Table 1. In Examples 1-9, the lowest 200 cycle efficiency is Example 4, which is 96.5%, and the highest cycle efficiency is Example 1, which is 98.1%; and in Comparative Examples 1-5, the highest 200 cycle efficiency is Comparative Example 5, which is 87.4. It can be seen that when the technical solution of the present application is adopted, the lowest value of the 200 cycle efficiency is still 9.1% higher than the best performing prior art Comparative Example 5. Therefore, the present application can significantly improve the cycle efficiency of the sodium ion battery after coating with lanthanum and / or calcium.
[0147] On the other hand, the thickness change rate during the cycle in Examples 1-9 is the lowest in Example 9, with a value of 1.2%, and the highest in Examples 1 and 8, with a value of 2.6%; while in Comparative Examples 1-5, the thickness change during the cycle is all above 4.4%. This is because after coating with lanthanum and / or calcium, the residual alkali on the surface of the positive electrode material is reduced, thereby reducing the side reaction between the positive electrode material and the electrolyte, thereby greatly reducing the thickness change rate during the cycle.
[0148] Therefore, in the present application, the structural stability of the positive electrode material is significantly improved through the interface design of La and / or Ca composite coating, and the cycle capacity retention rate is significantly improved compared with the comparative example.
[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0150] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material comprises a core and a shell, wherein the shell covers the core; the chemical formula of the core is Na a Ni x Fe y Mn z M 1-x-y-z O2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1; the chemical formula of the shell is NaLa r Ca 1-r O2, where 0<r<1; In the core, the M element includes one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, and B.
2. A method for preparing the positive electrode material for a sodium ion battery according to claim 1, characterized in that: include: A solution of a nickel source, a manganese source, an iron source and an M element source is mixed, a pH adjuster is added, and a hydroxide precursor is obtained by a coprecipitation method; The hydroxide precursor is mixed with a sodium source, and then subjected to a first calcination, followed by cooling to obtain a first calcined product; The first calcined product is mixed with a calcium source and a lanthanum source and then subjected to a second calcination to obtain the sodium ion battery positive electrode material.
3. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: At least one of the following conditions is met: a. The nickel source comprises nickel sulfate, the manganese source comprises manganese sulfate, and the iron source comprises iron sulfate; b. The M element source includes sulfates of one or more of Al, Mg, Ti, Zr, Y, La, Ca, Zn, Cu, W, Li, and B; c. The pH adjuster includes at least one of aqueous ammonia and sodium hydroxide; d. Using the pH adjuster to adjust the pH value of the system to 8.0-12.0; e. After the hydroxide precursor is prepared, the process further includes solid-liquid separation, washing, and drying. The temperature during the drying process is 100-300° C. and the time is 2-6 hours.
4. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: At least one of the following conditions is met: f. The chemical formula of the hydroxide precursor is Ni x Fe y Mn z M 1-x-y-z (OH)2, wherein 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0; g. The chemical formula of the first calcined product is Na a Ni x Fe y Mn z M 1-x-y-z O2, where 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.
0.
5. The method for preparing a positive electrode material for a sodium ion battery according to claim 4, characterized in that: At least one of the following conditions is met: h. The mixing ratio of the hydroxide precursor and the sodium source is a molar ratio of the metal cation in the hydroxide precursor to the sodium ion of 1:n, wherein 0.95≤n≤1.4; i. The lanthanum source comprises La2O3; j. The calcium source includes CaCl2, CaCO3, CaO, Ca(OH), CaF2; k. The lanthanum source and the calcium source are nano-scale particles.
6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: At least one of the following conditions is met: l. The first calcination is a multi-stage calcination; m. The calcination atmosphere of the first calcination comprises air and oxygen; n. The second calcination temperature is 300-600°C and the time is 5-10h.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The multi-stage calcination process includes: raising the temperature to 400-550°C at a heating rate of 1.5-7°C / min for pre-sintering, and the pre-sintering time is 4-8h; then raising the temperature to 800-1100°C at a heating rate of 1.5-7°C / min for sintering, and the sintering time is 10-24h; cooling to room temperature after sintering.
8. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: After the second calcination, the coating amount of the calcium element is 300-2000 ppm, and the coating amount of the lanthanum element is 300-2000 ppm.
9. A sodium ion battery, characterized in that: The raw materials include the sodium ion battery positive electrode material according to claim 1.
10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material and sodium-ion battery containing same
CN116417597A
Sodium-ion battery positive electrode material and preparation method thereof, positive electrode and sodium-ion battery
CN116741984A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117423825A
High-nickel sodium ion positive electrode material and preparation method and application thereof
CN118610429A
Cited By
Sodium-ion battery positive electrode active material, preparation method thereof and sodium-ion battery
CN120545353A
Sodium ion battery positive electrode active material and preparation method thereof, sodium ion battery
CN120545353B
Sodium electrode layered oxide and preparation method and application thereof
CN120664605A
Sodium-ion battery positive electrode material with core-shell structure and preparation method of sodium-ion battery positive electrode material
CN120784312A
Sodium-ion battery positive electrode material and preparation method thereof, pole piece and battery
CN121260769A